RETRACTED: Assisting Smart Construction With Reliable Edge Computing Technology - Qiang Yue; Song Mu; Longguan Zhang; Zhun Wang; Zhun Wang; Zhonghua Zhang; Xing Zhang; Yongge Wang; Yongge Wang; Zhuang Miao; Zhuang Miao (Frontiers in Energy Research)
Although smart construction tools are already assisting the construction sector, still major reforms are considerably seen in the coming years with Artificial Intelligence of Things (AIoT). The purpose of this work was to develop a down-to-earth reliable edge-computing design and plan, which can be utilized to bolster savvy development situations with high quality of service. The number of devices connected to industrial processes is growing in tandem with the advancement of sophisticated technologies and the use of the AIoT. Big data are created as gadgets grow more integrated and need more computing power. However, as the amount of big data generated grows, processing and analytical issues arise. Cloud computing technologies are now being used to solve processing and analytical challenges. However, by using edge computing technologies, greater emphasis is placed on executing calculations as near to the device as feasible. As a result of these facts, this article suggests the arrangement plan, which depends on the most recent cloud and computer program designing approaches and advances, and gives flexibility, interoperability, and adjustment to construction companies' particular needs.